Effects of mindfulness-based stress reduction on anxiety symptoms in young people: A systematic review and meta-analysis. (July 2020) - Zhou, Xiang; Guo, Jieyu; Lu, Guangli; Chen, Chaoran; Xie, Zhenxing; Liu, Jiangmin; Zhang, Chuning
Highlights: MBSR significantly reduced anxiety symptoms at post treatment. The effect of MBSR on anxiety symptoms in young people may be affected by intervention duration. The effects of long-term intervention and follow-up in young people need further investigation. Abstract: In this study, we evaluated the efficacy of mindfulness-based stress reduction (MBSR) for young people with anxiety symptoms. We used many databases, including PubMed, PsycINFO, Web of Science, EMBASE, CINAHL and Cochrane Library (from inception to May 2019). We included randomized controlled trials (RCTs) comparing MBSR with various control conditions, including didactic lecture course, health education, treatment as usual, didactic seminar and cognitive behavioral program in young people with anxiety symptoms. Finally, we selected fourteen studies comprising 1489 participants comparing with control conditions. The meta-analysis suggested that MBSR significantly reduced anxiety symptoms compared to control conditions at post-treatment (Standardized Mean Difference, SMD = –0.14, 95% CI –0.24 to –0.04). However, the effect of MBSR on anxiety symptoms in young people may be affected by different intervention duration, especially the significance in a short-term intervention (less than 8 weeks). In addition, the meta-analysis indicated publication bias for anxiety symptoms. Using the trim-and-fill method, we found the adjusted standardized mean difference, which indicated that MBSR was still significantly superior to the other control conditions. The sensitivity analysis showed that the result was reliable. Current evidence indicates MBSR has superior efficacy compared with control conditions in treating young people with anxiety symptoms. Based on this, we suggest there is a significant effect of MBSR on young people with anxiety symptoms, especially the effects of long-term intervention for future studies.